A cohort-based multi-omics identifies nuclear translocation of eIF5B /PD-L1/CD44 complex as the target to overcome Osimertinib resistance of ARID1A-deficient lung adenocarcinoma - Dantong Sun; Helei Hou; Feiyue Feng; Weizheng Wu; Jingyu Tan; Tongji Xie; Jiayu Liu; Jinsong Wang; Haili Qian; Junling Li; Puyuan Xing (Experimental Hematology & Oncology)
Abstract Background Osimertinib has emerged as a critical element in the treatment landscape following recent clinical trials. Further investigation into the mechanisms driving resistance to Osimertinib is necessary to address the restricted treatment options and survival advantages that are compromised by resistance in patients with EGFR-mutated lung adenocarcinoma (LUAD). Methods Spatial transcriptomic and proteomic analyses were utilized to investigate the mechanisms of Osimertinib resistance. Co-IP, MS, RNA-seq, ChIP-seq, RIP-seq, and ATAC-seq were performed in cell lines to further explore the mechanism. To validate the findings, in vitro and in vivo molecular experiments were conducted. Results We found that the ARID1A deficiency results in resistance to Osimertinib by hindering programmed cell death through the EZH2/PTEN/E2F1 axis. This altered axis influences PD-L1 transcription through E2F1-mediated promoter activation and PD-L1 translation via the MDM2/eIF5B/PD-L1 axis. Subsequently, ARID1A deficiency results in increased expression of eIF5B and Importin-β1, promoting PD-L1 nuclear-translocation. The nuclear PD-L1 (nPD-L1) interacts with CD44, leading to nPD-L1 complex formation, activation of the RASGEF1A promoter, initiation of the Ras pathway, and contributing to Osimertinib resistance. Targeting the transcription, translation and nuclear-translocation of PD-L1 using lipid nanoparticles (LNPs) overcomes ARID1A deficiency-induced resistance. Conclusion ARID1A deficiency promotes PD-L1 nuclear translocation and induces Osimertinib resistance.